Aesthetics of Repetition in âAn Address from the Market of Idlenessâ by SamÄ«h Al-QÄsim - Ali Asghar Ghahramani Moghbel (دراسات فی اللغه العربیه و آدابها)
In Arabic poetry, the device of repetition functions at two levels: form and meaning. In form, repetition makes for musical richness, and in meaning, it makes for emphasis. The present article is a study of repetition in âAn Address from the Market of Idlenessâ by Palestinian poet SamÄ«h Al-QÄsim. The poem depicts actual and possible Palestinian sufferings inflicted by Israelis and stresses that the poetâs resistance against the enemy will not be affected. In this article, the device of repetition is studied by considering repeated words, phrases and similar verb forms, and the poetâs intention in using repetition.